2014
DOI: 10.4238/2014.march.24.4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the growth arrest-specific homeobox gene Gax inhibits proliferation, migration, cell cycle progression, and apoptosis in serum-induced vascular smooth muscle cells

Abstract: ABSTRACT. The Gax gene has been implicated in a variety of celldevelopmental and biological processes, and aberrant Gax expression is linked to many diseases. In this study, to provide important insights for Gax-based gene therapy in vein graft restenosis and its anti-restenotic mechanism, we used rabbit vascular smooth muscle cells (VSMCs) to investigate the effects of Gax overexpression on proliferation, migration, cell cycle, and apoptosis in a serum-stimulated culture. Rabbit VSMC lines that stably overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…HOX gene, as a transcription factor, can combine with target DNA, regulating downstream gene expression involved in angiogenesis and repair, which closely related to proliferative vascular disease pathogenesis (Zheng et al, 2014). So, whether vessel proliferative disease induced by HCMV is related with HOX genes?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOX gene, as a transcription factor, can combine with target DNA, regulating downstream gene expression involved in angiogenesis and repair, which closely related to proliferative vascular disease pathogenesis (Zheng et al, 2014). So, whether vessel proliferative disease induced by HCMV is related with HOX genes?…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that HOX genes participate in a variety of cell proliferation and migration by direct or indirect way, i.e., over expression of growth arresting-specific homeobox (Gax) inhibits the proliferation and migration VSMCs induced by serum (Zheng et al, 2014). And the expression of HOXC11 can induce cell proliferation in renal cell carcinoma (Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Uncontrolled neointimal tissue accumulation of VSMCs shows some similarity with the tumor cell growth and benign tissue proliferation [ 35 ]. Thus, the regulation of apoptosis has attracted considerable attention as an effective way to eliminate hyper-proliferative VSMCs in neointimal formation [ 11 13 , 36 38 ]. While investigating the pro-apoptotic effect of EPOs, we initially observed that EPO-B and EPO-D potently inhibited PDGF-BB-induced VSMC proliferation in a dose- and time-dependent manner, consistent with previous studies [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mitotic catastrophe of VSMCs was determined by DAPI staining as previously described [ 11 ]. In brief, cells were cultured on an eight chambered glass culture slide (BD Biosciences) at a density of 1 × 10 4 cells/well and cultured for 24 h, and then cells were serum starved for 12 h prior to the treatment with EPO-B or EPO-D (1 to 100 nM), PTX (100 nM), or DMSO (final concentration of 0.1%) as a vehicle control in the presence of PDGF-BB (50 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation